The role of the rapid development of social consciousness in socio-cultural changes in modern society (Journal of Philosophy Culture and Political Science, 2018)
The purpose, main trends and ideas of the research are to show the rapid development of social consciousness plays an important role in socio-cultural changes in modern society. The scientific significance of the work are that it will develop existential bases of modernization of the public consciousness. Scientific understanding of the phenomena occurring in the world and in the country events will allow people in practice to adapt to changes at work, home, leisure, housing, ways of human communication. The solution to these issues should contribute to the development of national social philosophy. Practical meaning of results of work is expressed in the possibility to develop a new discipline «Modernization of Kazakhstan’s identity».Key words: sociality, culture, modernization, society, identity.